Pathogenesis of Multiple Organ Injury in COVID-19 and Potential Therapeutic Strategies - Lopes-Pacheco, Miquéias; Silva, Pedro Leme; Cruz, Fernanda Ferreira; Battaglini, Denise; Robba, Chiara; Pelosi, Paolo; Morales, Marcelo Marcos; Caruso Neves, Celso; Rocco, Patricia Rieken Macedo (Frontiers in Physiology, 2021)
Severe acute respiratory disease coronavirus 2 (SARS-CoV-2, formerly 2019-nCoV) is a novel coronavirus that has rapidly disseminated worldwide, causing the coronavirus disease 2019 (COVID-19) pandemic. As of January 6th, 2021, there were over 86 million global confirmed cases, and the disease has claimed over 1.87 million lives (a ~2.2% case fatality rate). SARS-CoV-2 is able to infect human cells by binding its spike (S) protein to angiotensin-conversing enzyme 2 (ACE2), which is expressed abundantly in several cell types and tissues. ACE2 has extensive biological activities as a component of the renin-angiotensin-aldosterone system (RAAS) and plays a pivotal role as counter-regulator of angiotensin II (Ang II) activity by converting the former to Ang (1-7). Virion binding to ACE2 for host cell entry leads to internalization of both via endocytosis, as well as activation of ADAM17/TACE, resulting in downregulation of ACE2 and loss of its protective actions in the lungs and other organs. Although COVID-19 was initially described as a purely respiratory disease, it is now known that infected individuals can rapidly progress to a multiple organ dysfunction syndrome. In fact, all human structures that express ACE2 are susceptible to SARS-CoV-2 infection and/or to the downstream effects of reduced ACE2 levels, namely systemic inflammation and injury. In this review, we aim to summarize the major features of SARS-CoV-2 biology and the current understanding of COVID-19 pathogenesis, as well as its clinical repercussions in the lung, heart, kidney, bowel, liver, and brain. We also highlight potential therapeutic targets and current global efforts to identify safe and effective therapies against this life-threatening condition.